The Antimicrobial Peptide Capitellacin: Chemical Synthesis of Analogues to Probe the Role of Disulphide Bridges and Their Replacement with Vinyl Sulphides - Oscar A. Shepperson; Paul W. R. Harris; Margaret A. Brimble; Alan J. Cameron (MDPI AG, 2024)
Capitellacin (1) is a 20-residue antimicrobial β-hairpin, produced by the marine polychaeta (segmented worms) Capitella teletai. Since its discovery in 2020, only very limited studies have been undertaken to understand capitellacin's structure-activity relationship (SAR). Using fast-flow Fmoc-SPPS, a focused library of capitellacin analogues was prepared to systematically study the influence of the two disulphide bridges on its structure and activity, and their replacement with a vinyl sulphide as a potential bioisostere. Upon studying the resulting peptides' antimicrobial activity and secondary structure, the most terminal disulphide emerged as the most critical element for maintaining both bioactivity and the secondary structure, properties which were demonstrated to be closely interlinked. The removal of the innermost disulphide bridge or disulphide replacement with a vinyl sulphide emerged as strategies with which to tune the activity spectrum, producing selectivity towards E. coli. Additionally, an enantiomeric d-capitellacin analogue revealed mechanistic insights, suggesting that chirality may be an inherent property of capitellacin's bacterial membrane target, or that a hitherto unknown secondary mechanism of action may exist. Additionally, we propose the Alloc protecting group as a more appropriate alternative to the common Dde group during fast-flow Fmoc-SPPS, in particular for short-chain diamino acids.